2010
DOI: 10.1016/j.taap.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of proliferative and inflammatory markers in a full-thickness human skin equivalent following exposure to the model sulfur mustard vesicant, 2-chloroethyl ethyl sulfide

Abstract: Sulfur mustard is a potent vesicant that induces inflammation, edema and blistering following dermal exposure. To assess molecular mechanisms mediating these responses, we analyzed the effects of the model sulfur mustard vesicant, 2-chloroethyl ethyl sulfide, on EpiDerm-FT™, a commercially available full-thickness human skin equivalent. CEES (100–1000 μM) caused a concentration-dependent increase in pyknotic nuclei and vacuolization in basal keratinocytes; at high concentrations (300–1000 μM), CEES also disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 73 publications
8
32
0
Order By: Relevance
“…NM exposure resulted in upregulation of iNOS and COX-2 in basal and superbasal cells after 1–3 days. Increases in COX-2 expression are consistent with previous findings that sulfur mustard, and the related half mustard, 2-chloroethyl ethyl sulfide, stimulate the release of prostaglandins from human and mouse keratinocytes, and that in mouse skin, sulfur mustard-induced injury is associated with increased COX-2 (Black et al, 2010; Joseph et al, 2011; Lefkowitz and Smith, 2002). While sebocytes continued to express iNOS and COX-2 for 1 day post NM, subsequently they degenerated.…”
Section: Discussionsupporting
confidence: 90%
“…NM exposure resulted in upregulation of iNOS and COX-2 in basal and superbasal cells after 1–3 days. Increases in COX-2 expression are consistent with previous findings that sulfur mustard, and the related half mustard, 2-chloroethyl ethyl sulfide, stimulate the release of prostaglandins from human and mouse keratinocytes, and that in mouse skin, sulfur mustard-induced injury is associated with increased COX-2 (Black et al, 2010; Joseph et al, 2011; Lefkowitz and Smith, 2002). While sebocytes continued to express iNOS and COX-2 for 1 day post NM, subsequently they degenerated.…”
Section: Discussionsupporting
confidence: 90%
“…In SEs, PCNA is usually expressed in the basal layer [Black et al, 2010]. Consistent with this, PCNA was mainly detected in the basal layer of the control model.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have shown that SM induces DNA double strand breaks, a process that activates DNA repair (Black et al, 2010; Jowsey et al, 2010). Histone phospho-H2A.X binds to double stranded DNA breaks creating a repair recognition domain that is important in controlling DNA damage (Clingen et al , 2008; Mah et al , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that SM treatment of mouse epidermis causes rapid (within 1 day) increases in expression of phospho-H2A.X in the nucleus of basal keratinocytes (Joseph et al , 2011). The half mustard, 2-chloroethylethylamine, also induces phospho-H2A.X in basal keratinocytes of human full-skin constructs (Black et al, 2010). The present studies demonstrate that SM also induces double strand DNA breaks in hair follicles and sebaceous glands within 1 day of treatment.…”
Section: Discussionmentioning
confidence: 99%